2021
DOI: 10.3389/fped.2021.808317
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Support of Infants With Congenital Diaphragmatic Hernia

Abstract: Optimisation of respiratory support of infants with congenital diaphragmatic hernia (CDH) is critical. Infants with CDH often have severe lung hypoplasia and abnormal development of their pulmonary vasculature, leading to ventilation perfusion mismatch. It is vital that lung protective ventilation strategies are employed during both initial stabilisation and post-surgical repair to avoid ventilator induced lung damage and oxygen toxicity to prevent further impairment to an already diminished gas-exchanging env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 64 publications
1
15
0
1
Order By: Relevance
“…Previous studies have shown that insufficient gas exchange within 24 h after birth is a risk factor for CDH neonates (22), suggesting that children with high MSA levels need close monitoring and prompt intervention early after birth to maintain improvement in oxygenation. We found that the MSA level was associated with the duration of mechanical ventilation, consistent with previous studies (23), illustrating that MSA values could reflect the severity of lung hypoplasia (24).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that insufficient gas exchange within 24 h after birth is a risk factor for CDH neonates (22), suggesting that children with high MSA levels need close monitoring and prompt intervention early after birth to maintain improvement in oxygenation. We found that the MSA level was associated with the duration of mechanical ventilation, consistent with previous studies (23), illustrating that MSA values could reflect the severity of lung hypoplasia (24).…”
Section: Discussionsupporting
confidence: 91%
“…Although there was no reduction in BPD at 36 weeks, surfactant-treated infants had fewer episodes of rehospitalisation over the first year of life [209]. Routine surfactant therapy is not recommended in infants with congenital diaphragmatic hernia [210].…”
Section: Introductionmentioning
confidence: 99%
“…In each mode (NAVA and SIMV), the esophageal and transdiaph- [1], the maximal inspiratory EAdi value [2], the end of neural inspiration [3], and at the end of neural expiration [4], flow (beginning [5] and end [6]), and esophageal pressure (beginning [7] and end [8]). EAdi, the electrical activity of the diaphragm; NAVA, neurally adjusted ventilatory assist.…”
Section: Measurements and Recordingsmentioning
confidence: 99%
“…After surgical repair, it is also very important to avoid ventilator‐induced lung damage to prevent further impairment of the diaphragm and the lung, 4 and neurally adjusted ventilatory assist (NAVA; Maquet, Getinge) has been proposed to achieve this goal 5 . NAVA is a ventilatory mode that delivers synchronized assisted ventilation, proportional to the respiratory drive, using the electrical activity of the patient's diaphragm (EAdi) 6 .…”
Section: Introductionmentioning
confidence: 99%